Rounding Phenomenon in the OTC Market - He, Daoping; Tian, Yao; Liu, Caixing (Journal of Accounting and Finance, 2021)
This study investigates the rounding phenomenon in the over-the-counter (OTC) market and finds that (1) similar to firms listed in the major U.S. stock markets, OTC-listed firms manipulate their reported earnings and revenues through rounding; (2) rounding manipulation is more severe in the OTC market than in the major stock markets and (3) the enforcement of SEC’s mandatory disclosure requirements in 1999 reduced OTC firms’ rounding manipulation activities. This study extends the rounding manipulation literature and provides the first piece of empirical evidence of rounding manipulation in the OTC market. It helps scholars and investors better understand firms in the OTC market. This study also provides feedback to policy makers and regulators on the effectiveness of the SEC mandatory disclosure requirement on OTC firms’ financial reporting quality.